The Procurement Perspectives of Fruits and Vegetables Supply Chain Planning - Bikram Kumar Bahinipati (International Journal of Supply Chain Management, 2014)
Supply chain planning in the fruits and vegetables (FV) supply chains, dealing with short life cycled products in a competitive marketplace, integrates the complex network farmers, food processing and supply to end customers to enhance operations effectiveness.